PENINGKATAN KETERAMPILAN PENATAAN MEJA PRASMANAN (BUFFET) MELALUI METODE DEMONSTRASI BERBASIS ANIMASI - Eka Priantini (JS (JURNAL SEKOLAH), 2019)
Abstract: Improvement of Buffet Table Arrangement Skills through Animation-Based Demonstration Methods. Skills can make students creative and independent. In vocational schools skills are preferred. With the application of the animation-based demonstration method, it has made a major contribution in improving students' skills in the subject matter, especially the basic competency in arranging the buffet table, XII students of SMKN 3 Pekanbaru. From the results of observations in the first and second cycles obtained 66.7% of students completeness, in the second cycle 93.33% completeness of students. Here an increase of 26.63% completeness of students. The use of animation-based demonstration methods not only until the second cycle, but can be used continuously to obtain maximum results. Keywords: skills, arrangement of buffet tables, demonstration methods Abstrak: Peningkatan Keterampilan Penataan Meja Prasmanan (Buffet) Melalui Metode Demonstrasi Berbasis Animasi. Keterampilan dapat menjadikan siswa kreatif dan mandiri. Pada sekolah kejuruan keterampilan sangat diutamakan. Dengan penerapan metode demontrasi berbasis animasi memberikan kontribusi yang besar dalam peningkatan keterampilan siswa pada mata pelajaran tata hidang terutama kompetensi dasar penataan meja prasmanan (buffet), siswa XII Tata Boga SMKN 3 Pekanbaru. Dari hasil observasi pada siklus I dan II diperoleh hasil 66.7 %  ketuntasan siswa, pada siklus II  93.33 % ketuntasan siswa. Disini terjadi peningkatan sebesar 26.63 % ketuntasan siswa. Penggunaan metode demontrasi berbasis animasi tidak hanya sampai siklus II saja, tetapi bisa digunakan secara berkesinambungan untuk memperoleh hasil yang maksimal. Kata Kunci: keterampilan, penataan meja prasmanan, metode demonstrasi